Continuum Limit for a Discrete Hodge–Dirac Operator on Square Lattices - Miranda-Rozas, P (Springer Science and Business Media B.V., 2023)
We study the continuum limit for Dirac–Hodge operators defined on the n dimensional square lattice hZn as h goes to 0. This result extends to a first order discrete differential operator the known convergence of discrete Schrödinger operators to their continuous counterpart. To be able to define such a discrete analog, we start by defining an alternative framework for a higher–dimensional discrete differential calculus. We believe that this framework, that generalize the standard one defined on simplicial complexes, could be of independent interest. We then express our operator as a differential operator acting on discrete forms to finally be able to show the limit to the continuous Dirac–Hodge operator. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.